Retracted: Pengembangan Media Papan Catur Digital untuk Materi Bangun Ruang Kelas VI Sekolah Dasar - Farhan Aditya Hasbi (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2021)
Following a rigorous, carefully concerns and considered review of the article published in Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan to article entitled “Pengembangan Media Papan Catur Digital untuk Materi Bangun Ruang Kelas VI Sekolah Dasar” Vol. 1(12), 2021, 962–967. This paper has been found to be in violation of the Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan Publication principles and has been retracted. The document and its content has been removed from Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, and reasonable effort should be made to remove all references to this article.